Effect of play-based intervention on children's mental status and caregiver involvement during hospitalization: findings from Pakistan - Vardah Noor Ahmed Bharuchi; Muneera A. Rasheed (BMC, 2024)
Abstract Background The nurturing care framework (NCF) encompasses responsive caregiving, health, nutrition, safety and security by parents and other caregivers. It improves health, development and wellbeing of children. A hospital environment can be detrimental to the developmental and emotional needs of children hence NCF can be applied to hospitalized children. Objective The objective was to determine if (i) play stimulation intervention mediated by non-specialist providers (caregivers) improves mental status of children who are hospitalized; (ii) to examine if difference varies between different providers and iii) if there is variation based on child age and criticalness of illness. Method A one-group pretest-posttest research was carried out using purposive sampling in a pediatric unit in Karachi, Pakistan, from November 2017 to December 2019. Children aged 3 months to 6 years were offered play stimulation by trainee psychologists. The outcome was measured through an observation tool, the Mental Status Examination Scale (MSE-S) developed for the study. Results A total of 524 sessions were delivered to 351 children. Significant mean difference was observed on MSE-S before and after the intervention when it was provided by trainees (9.95, CI = 8.11, 11.7), mothers (mean difference = 5.86, CI = 5.30, 6.42), fathers (mean difference = 5.86, CI = 4.48, 7.24) and non-specialist providers [caregivers (mean difference = 5.40, CI = 3.91, 6.89). Significant differences in mean was observed on MSE-S across different age groups and criticalness of illness. Conclusion It was concluded that play stimulation not only affects the behaviour of children but also varies when delivered by caregivers and trainees. Hence, interventions that involve parents are feasible.